2019
DOI: 10.21037/qims.2019.03.04
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of qualitative and quantitative shear wave elastography in differentiating malignant from benign breast masses, and association with the histological prognostic factors

Abstract: Background: To determine the diagnostic performance of qualitative and quantitative shear wave elastography (SWE) and the optimal cutoff values of the quantitative SWE parameters in differentiating malignant from benign breast masses, and to evaluate the association between the quantitative SWE parameters and histological prognostic factors. Methods: A gray scale ultrasound and SWE were prospectively performed on a total of 244 breast masses (148 benign, and 96 malignant) in 228 consecutive patients before an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 33 publications
6
25
1
Order By: Relevance
“…SWE could quantitatively evaluate the elastic characteristics of breast lesions and more accurately judge the benign and malignant breast lesions. Our study showed that there were signi cant differences in elastic characteristics between benign and malignant breast lesions, which were the same as those of previous studies [8,20]. For malignant breast lesions, a large number of cancer cells proliferated, invaded and in ltrated the normal breast stroma and adipose tissue, and interacted with the tumor microenvironment, causing complex connective tissue hyperplasia and brosis, which were important typical pathological changes in the process of tumor development and invasion, they could lead to overexpression and accumulation of ECM components, rearrangement and cross-linking of ECM structure [21,22], and increase the stiffness of the lesions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…SWE could quantitatively evaluate the elastic characteristics of breast lesions and more accurately judge the benign and malignant breast lesions. Our study showed that there were signi cant differences in elastic characteristics between benign and malignant breast lesions, which were the same as those of previous studies [8,20]. For malignant breast lesions, a large number of cancer cells proliferated, invaded and in ltrated the normal breast stroma and adipose tissue, and interacted with the tumor microenvironment, causing complex connective tissue hyperplasia and brosis, which were important typical pathological changes in the process of tumor development and invasion, they could lead to overexpression and accumulation of ECM components, rearrangement and cross-linking of ECM structure [21,22], and increase the stiffness of the lesions.…”
Section: Discussionsupporting
confidence: 91%
“…Shear wave elastography (SWE) is a new ultrasound technology based on conventional ultrasound, which quanti es the tissue stiffness information with speci c numerical values [7]. And its value in differential diagnosis of benign and malignant breast lesions has been proved by many studies [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI), ultrasonography, and mammography are key modalities for breast tumor diagnosis and the subsequent choice of appropriate therapy (5). MRI is highly sensitive to the detection of breast cancer and is the most sensitive technique for screening highrisk women and detecting contralateral or multifocal disease (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Breast magnetic resonance imaging (MRI) is a more sensitive modality to detect benign and malignant breast lesions compared with mammography and ultrasound, especially in young patients with a dense mammary gland (13,14). In patients undergoing NAC, breast MRI is also an efficient noninvasive method in evaluating the efficacy of chemotherapy (15).…”
Section: Introductionmentioning
confidence: 99%